Phase I/II trial of bevacizumab and radiotherapy for locally advanced inoperable colorectal cancer: vasculature-independent radiosensitizing effect of bevacizumab - Koukourakis, Michael I; Giatromanolaki, Alexandra; Sheldon, Helen; Buffa, Francesca M; Kouklakis, George; Ragoussis, Ioannis; Sivridis, Efthimios; Harris, Adrian L (Clinical cancer research, 2009)
Anti-vascular endothelial growth factor therapy enhances the activity of radiotherapy in experimental models, and bevacizumab has therapeutic activity in patients with metastatic colorectal cancer. Twenty-two patients with locally advanced inoperable colorectal carcinomas (LA/I-CRC) were treated with conformal hypofractionated (3.4 Gy/fraction x 15) split-course accelerated radiotherapy (biological equivalent dose, 67.2 Gy) supported with amifostine, capecitabine (600 mg/m2 daily, 5 days/week), and bevacizumab (5 mg/kg every 2 weeks, five cycles). Biopsies from nine patients, performed before and 1 week after bevacizumab administration, were analyzed for changes in mRNA expression with Illumina gene arrays. No serious grade 3 chemotherapy-related side effects were recorded. There was low acute toxicity, with moist perineal desquamation noted in 2 of 22 patients, diarrhea grade 2 to 3 in 5 of 22 patients, and severe proctalgia in 2 of 22 patients. One patient died from Fournier's gangrene before treatment completion. Within a median follow-up of 18 months, two patients with preradiotheraphy direct involvement of adjacent organs expressed recto-vaginal/perineal fistula. Out of 19 evaluable cases, 13 (68.5%) showed complete response and 4 showed (21.1%) partial response. Fourteen patients are alive with no evidence of loco-regional relapse. In the gene array analysis, 30 known genes associated with transcription factors, DNA repair, and proliferation were downregulated by bevacizumab. DUSP1 gene was the most consistently downregulated transcript. The combination of radiotherapy with bevacizumab is feasible and results in a high rate of durable complete responses in patients with LA/I-CRC. Radiosensitization may occur through a direct effect on tumor cells followed by a wide scale suppression of transcription factors and genes involved in DNA repair and proliferation.